2009
DOI: 10.1007/s11256-009-0138-x
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in College Preparedness: A Statewide Study

Abstract: In this study, the authors investigated the extent to which boys and girls differed in their college-ready performance in reading, in math, and in both subjects for the 2006-2007 school year for the state of Texas (n = 1,099 high schools). Also examined were the extent to which boys and girls differed in their performance on the Scholastic Assessment Test (SAT) and the American College Test (ACT) for the 2005-2006 and 2006-2007 school years. Differences in criterion scores, as well as how many boys and girls … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 26 publications
(36 reference statements)
3
17
0
Order By: Relevance
“…On the CPT Reading and Math scores, post hoc analysis revealed that the White group had higher mean scores than the African American group, while the Hispanic group had higher group mean scores than the Caribbean group. Although the White group only comprised 8% of the total, the fact that they scored higher on CPT Reading and Math is consistent with previous research (Combs et al, 2010), which found that Whites tended to outperform other ethnic groups in both math and science.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…On the CPT Reading and Math scores, post hoc analysis revealed that the White group had higher mean scores than the African American group, while the Hispanic group had higher group mean scores than the Caribbean group. Although the White group only comprised 8% of the total, the fact that they scored higher on CPT Reading and Math is consistent with previous research (Combs et al, 2010), which found that Whites tended to outperform other ethnic groups in both math and science.…”
Section: Discussionsupporting
confidence: 89%
“…The study by Combs et al, 2010, which used SAT and ACT data from 1,009 high schools in The results of the data analysis with respect to demographics also revealed group mean differences in CGPA, CPT Math, CPT Reading, and PGPA by ethnic origin. On the CPT Reading and Math scores, post hoc analysis revealed that the White group had higher mean scores than the African American group, while the Hispanic group had higher group mean scores than the Caribbean group.…”
Section: Discussionmentioning
confidence: 99%
“…Central to AYP was the expectation that students in all subgroups would perform at a proficient level by 2014. Within this context in the past decade, several researchers have examined the achievement of students in various subgroups to shed light on variables related to equity and opportunity (see Combs et al 2009;Haas and Slate 2010;Moore et al 2010;Rojas-LeBouef and Slate 2010).…”
mentioning
confidence: 99%
“…Combs, Slate, Moore, Bustamante, Onwuegbuzie, and Edmonson (2010) found males to be more likely to score at or above college-ready benchmark scores on the ACT and SAT, using state-wide data from Texas. However, females were more likely to take the ACT or SAT than males (Combs et al, 2010).…”
Section: College Entrance Exams As a Measure Of College Readinessmentioning
confidence: 91%